"Family-friendly" tenancies in the private rented sector. Issue 3 (15th August 2019) - Walsh, Emily
Abstract : Purpose: This paper aims to analyse the extent to which the government's recent proposals to end no-fault evictions will result in "family-friendly" tenancies. Design/methodology/approach: It applies the theoretical scholarship on the meaning of family and home to the current law relating to private rented tenancies and the government's proposals to increase security of tenure in the private rented sector. Findings: Security of tenure is important to a number of the key aspects of home. However, feelings of home are better protected by security of occupancy, which requires more than de jure security of tenure. For families to feel at home in the private rented sector, they must be permitted to personalise their home and to keep pets. Further legislative changes could achieve these changes. However, for families to really make a home in the private rented sector, they need to exercise some choice over where they live and for low-income families; this will only be possible with broader policy changes. Originality/value: This paper contributes to the important scholarship on the meaning of home and applies this to the very current debate on the rights of tenants in the private rented sector.